METHODS OF METAPHOR TRANSFER IN THE PROCESS OF ADVERTISING SLOGANS TRANSLATION - Оlena М. Bondarevska (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
The paper focuses on comparing the original English slogans and short advertising texts in a recipient language with a view to identify whether the latter should be considered translations within the framework of the functional approach or cultural adaptations of original slogans. The scientific novelty of the study is determined by its complex nature: the present study is based on the cognitive approach to the translation of metaphors of multi-structural languages (Ukrainian and English) in order to identify the possibility of transferring to another language cultural experience and mentality that are embedded in the metaphor of the original language. Such interaction generates complex conceptual structures that form around the metaphorical core. Metaphor, as a linguistic and speech phenomenon, undoubtedly causes great theoretical and practical interest. The study of the nature of metaphorical transference, the analysis of the multifaceted language shifts that it causes, the consideration of the dependence of the metaphor on its syntagmatic and paradigmatic ties helps to penetrate the complex vocabulary system, to see the boundless possibilities of the formation of new lexical units hidden therein, to reveal the dynamics of semantic relations within the lexical system this synchronous cut. The study is based on the cognitive and linguo-culturological approaches to analysing slogans containning the metaphor. The research methodology includes the cognitive approach to translating the metaphor. So, as a result of comparing the original English-language slogans and short advertising texts in the language of the receptor, we came to the conclusion that Ukrainian-language slogans in most cases are the result of cultural adaptation of English-speaking short advertising texts. Among the main reasons for handling adaptation, it is important to note, first, the lack of an equivalent metaphor, as well as the possibility of co-keeping the original figurativeness. Secondly, the cultural adaptation of the initial short advertising texts may be dictated by the intention to rewrite the slogan in Ukrainian again in order to better convey the idea to the costumer. A multidimensional analysis of metaphor in slogans showed that the visual component of an advertising campaign plays no less a role than verbal or textual: advertising text can be played with using an image on a poster, thereby creating a construction of correspondences between elements and generating new complex conceptual structures.